2018
DOI: 10.1001/jamaophthalmol.2018.2466
|View full text |Cite
|
Sign up to set email alerts
|

Survival Rates in Patients After Treatment for Metastasis From Uveal Melanoma

Abstract: IMPORTANCE Despite high rates of local tumor control in patients who are treated for uveal melanoma, most patients will eventually die of metastasis. When metastasis develops, the liver is involved in most cases, and hepatic metastases are particularly refractory to treatment. Finding effective treatments has been challenging. A comparison of survival rates in patients who were treated for metastasis over approximately 30 years may offer insights into progress that has been made in prolonging survival. OBJECTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 23 publications
3
78
0
3
Order By: Relevance
“…Also, to the best of our knowledge, our cohort is the second largest one of patients receiving BSC for metastatic UM, and we are the first to stage them. We are aware of seven previous reports that included 11 to 191 patients with BSC [9,[20][21][22][23][24][25]. One of these studies also analysed prognostic factors and found, in line with us, that patients who received BSC had worse PS than actively treated [23].…”
Section: Discussionsupporting
confidence: 54%
“…Also, to the best of our knowledge, our cohort is the second largest one of patients receiving BSC for metastatic UM, and we are the first to stage them. We are aware of seven previous reports that included 11 to 191 patients with BSC [9,[20][21][22][23][24][25]. One of these studies also analysed prognostic factors and found, in line with us, that patients who received BSC had worse PS than actively treated [23].…”
Section: Discussionsupporting
confidence: 54%
“…Uveal melanoma is a rare neoplasia characterized by unpredictable behavior, and, despite the illusory success of local therapies, more than 50% of patients develop metastases within 5 years from diagnosis ( 31 ). Less than 4% of UM patients present metastases concomitant with the primary disease, but the high metastatic rate suggests that clinically undetectable metastases might be present upon diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Uveal melanoma is the most frequent primary intraocular tumour in adults (Singh & Topham 2003) with a reported incidence of 5-7 per million (Hu et al 2005) and must be considered as a severe ocular and, due to the risk of the development of metastases, possibly life-threatening condition (Lane et al 2018). To date, good local tumour control can be achieved in the vast majority of cases (Gragoudas et al 1992) using different techniques from eye-conserving plaque brachytherapy, proton beam therapy, stereotactic radiosurgery to enucleation.…”
Section: Introductionmentioning
confidence: 99%